Lethal outcome in elderly sexual violence: Escalation or different intent?. (November 2020) - Beauregard, Eric; Chopin, Julien; Winter, Jan
Highlights: Sexual murderers who killed the victims had the intent do so compared to those offenders who inflicted several physical injuries. Sexual murderers are more likely to use a weapon even if this is not necessary. Sexual murderers are more likely to steal from the victim Sexual abuse cases ending with a lethal outcome are not accidental or due to situational factors